Monocyte and macrophage foam cells in diabetes-accelerated atherosclerosis - Cervantes, Jocelyn; Kanter, Jenny E. (Frontiers in Cardiovascular Medicine, 2023)
Diabetes results in an increased risk of atherosclerotic cardiovascular disease. This minireview will discuss whether monocyte and macrophage lipid loading contribute to this increased risk as monocytes and macrophages are critically involved in the progression of atherosclerosis. Both uptake and efflux pathways have been described as being altered by diabetes or conditions associated with diabetes, which may contribute to the increased accumulation of lipids seen in macrophages in diabetes. More recently, monocytes have also been described as lipid-laden in response to elevated lipids, including triglyceride-rich lipoproteins, the class of lipids often elevated in the setting of diabetes.